Rancang Bangun Kuesioner Mengajar Guru Dengan Metode SAW Pada SMK Bhakti Kencana Tasikmalaya - Rian Ardiansah; Ai Ilah Warnilah (Universitas Bina Sarana Informatika, 2018)
Abstract - The development of technology and information is expanded very rapid. Media in presenting suggestions and critiques in the school is needed to improve the quality of teaching and learning activities. Submission of suggestions and criticisms can use the media of teachers performance appraisal questionnaire. Data processing results from existing questionnaires are computerized but there is no special application of questionnaires that process the data. Therefore, the author used Simple Additive Weighting (SAW) method to solve the problem. Students can filled out the teacher questionnaire through the online questionnaire, the data will be stored in database which will be processed until generate report automatically by system. In this research, the authors have made a special application of teachers perpformance questionnaires that can facilitate students in conducting assessments of the teacher. By using the media website and report directly after the students were done the assessment of the teachers. Processing of tachers performance questionnaire was a very helpful solution to the needs of users in producing information quickly and accurately. In addition, this application can displayed teacher ratings graph to facilitate the admin in knowing the results of the questionnaire. Keywords: Information systems, Questionnaires, Students, Teachers